2013
DOI: 10.1152/ajpgi.00278.2012
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal amniotic fluid intake reduces gut inflammatory responses and necrotizing enterocolitis in preterm neonates

Abstract: Preterm neonates are susceptible to gastrointestinal disorders such as necrotizing enterocolitis (NEC). Maternal milk and colostrum protects against NEC via growth promoting, immunomodulatory, and antimicrobial factors. The fetal enteral diet amniotic fluid (AF), contains similar components, and we hypothesized that postnatal AF administration reduces inflammatory responses and NEC in preterm neonates. Preterm pigs (92% gestation) were delivered by caesarean section and fed parental nutrition (2 days) followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 53 publications
4
58
0
1
Order By: Relevance
“…Although the concentrations of EGF we detected in rat amniotic fluid in our study were much lower (range 28 -141 pg/ml) than the nanogram concentrations tested by Good et al in their in vitro studies, the anti-inflammatory effects of amniotic fluid were similar in the two models. In another study, Siggers et al (34) showed that enteral administration of amniotic fluid in preterm pigs can reduce bacterial colonization, mucosal inflammatory responses, and NEC. In the present study, we show for the first time that amniotic fluid may promote epithelial restitution and prevent NEC-like injury and that these effects are mediated by HGF.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concentrations of EGF we detected in rat amniotic fluid in our study were much lower (range 28 -141 pg/ml) than the nanogram concentrations tested by Good et al in their in vitro studies, the anti-inflammatory effects of amniotic fluid were similar in the two models. In another study, Siggers et al (34) showed that enteral administration of amniotic fluid in preterm pigs can reduce bacterial colonization, mucosal inflammatory responses, and NEC. In the present study, we show for the first time that amniotic fluid may promote epithelial restitution and prevent NEC-like injury and that these effects are mediated by HGF.…”
Section: Discussionmentioning
confidence: 99%
“…Pig and human amniotic fluid, centrifuged so therefore presumed to be largely cell free, stimulate the proliferation and migration of rat intestinal epithelial cells in vitro [93]. In a well-established, clinically relevant model of spontaneous NEC in preterm piglets, postnatal minimal enteral feeding with porcine amniotic fluid decreased inflammation together with the incidence and severity of NEC [94], but had no effect when given later with full enteral feeding, although the beneficial effect during minimal enteral feeding was not consistently observed [93,94]. Another group has shown that enteral delivery of amniotic fluid decreases the severity of NEC in a mouse model [95].…”
Section: Preventionmentioning
confidence: 99%
“…In experimental models, the molecule C34, a 2-acetamidopyranoside (MW389) (44) and amniotic fluid (45) have reduced the incidence of experimental NEC. Epithelial growth factor (EGF) (46) and hepatocyte growth factors (HGF) (47) were found to be the mediators of amniotic fluid-derived protection. An improved understanding of the factors influencing the development of the microbiota or that modulate its composition may offer new strategies, tools, and opportunities for preterm interventions that reduce the risk of specific diseases as NEC.…”
Section: Reviewmentioning
confidence: 99%